2009
DOI: 10.1146/annurev.polisci.10.071105.095822
|View full text |Cite
|
Sign up to set email alerts
|

Redistricting: Reading Between the Lines

Abstract: The redistricting process evokes major questions about representative democracy, fairness, and political accountability. This article covers the state of the field along three dimensions. First, it explains how redistricting bears on questions about racial and minority representation. Second, it examines how redistricting influences electoral competition, focusing on the alleged power of partisans and incumbents to draw maps that eliminate all but token opposition. Third and last, it discusses the issues surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Casual observers of American politics are constantly bombarded with headlines about how contemporary legislative politics have become increasingly partisan. Whether due to the natural geographic sorting of voters into more ideologically homogeneous constituencies (e.g., Chen and Rodden, 2013; Dodd and Oppenheimer, 2017), gerrymandering (e.g., La Raja, 2009), or the general empowerment of party leaders (e.g., Aldrich and Rohde, 2017), many congressional scholars have suggested that parties in the United States Congress are more ideologically divergent than they have been for over a century (e.g., Hare and Poole, 2014). Likewise, scholars of political psychology (e.g., Hetherington and Rudolph, 2015) have argued that this increase in partisanship has corresponded to a decrease in trust across the parties, which makes the policymaking process increasingly contentious in Washington.…”
Section: Introductionmentioning
confidence: 99%
“…Casual observers of American politics are constantly bombarded with headlines about how contemporary legislative politics have become increasingly partisan. Whether due to the natural geographic sorting of voters into more ideologically homogeneous constituencies (e.g., Chen and Rodden, 2013; Dodd and Oppenheimer, 2017), gerrymandering (e.g., La Raja, 2009), or the general empowerment of party leaders (e.g., Aldrich and Rohde, 2017), many congressional scholars have suggested that parties in the United States Congress are more ideologically divergent than they have been for over a century (e.g., Hare and Poole, 2014). Likewise, scholars of political psychology (e.g., Hetherington and Rudolph, 2015) have argued that this increase in partisanship has corresponded to a decrease in trust across the parties, which makes the policymaking process increasingly contentious in Washington.…”
Section: Introductionmentioning
confidence: 99%
“…In our second application, we examine how residents define their COI by conducting an additional survey of 627 New York City residents. When drawing political districts for Congress, state legislatures, and city councils, many states and cities require inclusion of COI in the same district (La Raja 2009). The exact definition of COI varies, but they refer to groups of people who live in geographic proximity to one another and share political, economic, and other interests.…”
Section: Empirical Applicationsmentioning
confidence: 99%
“…Voters belonging to the opposing party or minorities might be "cracked" across several single-member districts to dilute their representation. On the other hand, "packing" them into overly concentrated districts into few districts also reduces their representation (La Raja, 2009). Redistricting can help parties improve the proportion of seats they win relative to their vote share and can help increase the electoral safety of incumbents -likely a contributor to significant increase in the reelection rate of House incumbents.…”
Section: Examining the Threats To Democracymentioning
confidence: 99%